The Impact of Inflation and Government Spending on Islamic Financial Growth in Indonesia 2015-2024 - Afifah, Yasmin; Nasution, Juliana; Daulay, Aqwa naser (Moneter: Jurnal Keuangan dan Perbankan, 2025)
This study seeks to explore how inflation affects and government expenditure on the improvement of Islamic finance in Indonesia during the period 2015–2024. This study utilizes a quantitative method with the application of multiple linear regression analysis with time series data. Annual data from 2015 to 2024 is used to test the proposed hypotheses. The result is according to the findings from the multiple linear regression analysis conducted on the data for 2015–2024, as well as the discussion outlined previously, the data allows for these conclusions is Inflation indicates a meaningful and positive impact on the growth of Islamic finance in Indonesia. These results indicate that rising inflation actually drives the growth of the Islamic finance market share. This is possible due to the growing public preference for value-based and stability-based financial systems, such as Islamic financing, which prioritizes the principles of fairness and is free from interest. Government consumption expenditure (state spending) also has a positive and significant impact on Islamic financial growth. This demonstrates that government fiscal intervention through public spending can expand access to Islamic financing, particularly in the productive sector and the lower-middle class. Simultaneously, inflation and government spending significantly influenced Islamic financial growth. With an R-squared value of 0.874, these two variables together explained 87.4% of the variation in Islamic financial growth during the study period.